A bioavailable form of curcumin suppresses cationic host defence peptides cathelicidin and calprotectin in a murine model of collagen-induced arthritis - Mahadevappa Hemshekhar; Dylan Lloyd; Hani El-Gabalawy; Neeloffer Mookherjee (Arthritis Research & Therapy, 2023)
Abstract Curcumin, a component of the South-Asian spice turmeric, elicits anti-inflammatory functions. We have previously demonstrated that a highly bioavailable formulation of cucurmin, Cureit/Acumin™ (CUR), can suppress disease onset and severity, in a collagen-induced arthritis (CIA) mouse model. In a previous study, we have also shown that the abundance of antimicrobial host defence peptides, specifically cathelicidin (CRAMP) and calprotectin (S100A8 and S100A9), is significantly increased in the joint tissues of CIA mice. Elevated levels of cathelicidin and calprotectin have been associated with the pathogenesis of rheumatoid arthritis. Therefore, in this study, we examined the effect CUR administration on the abundance of cathelicidin and calprotectin in the joints, in a CIA mouse model. Here, we demonstrate that daily oral administration of CUR significantly reduces the elevated levels of CRAMP and calprotectin to baseline in the joints of CIA mice. We also show a linear correlation between the abundance of these peptides in the joints with serum inflammatory cytokines TNFα, IFNγ, and MCP-1. Overall, our results suggest that oral administration of a bioavailable CUR can suppress cathelicidin and calprotectin in the joints and regulate both local (joints) and systemic (serum) inflammation, in inflammatory arthritis.